Changes in parenting strategies after a young person's self-harm: a qualitative study. Issue 1 (December 2016) - Ferrey, Anne; Hughes, Nicholas; Simkin, Sue; Locock, Louise; Stewart, Anne; Kapur, Navneet; Gunnell, David; Hawton, Keith
Abstract Background When faced with the discovery of their child's self-harm, mothers and fathers may re-evaluate their parenting strategies. This can include changes to the amount of support they provide their child and changes to the degree to which they control and monitor their child. Methods We conducted an in-depth qualitative study with 37 parents of young people who had self-harmed in which we explored how and why their parenting changed after the discovery of self-harm. Results Early on, parents often found themselves "walking on eggshells" so as not to upset their child, but later they felt more able to take some control. Parents' reactions to the self-harm often depended on how they conceptualised it: as part of adolescence, as a mental health issue or as "naughty behaviour". Parenting of other children in the family could also be affected, with parents worrying about less of their time being available for siblings. Many parents developed specific strategies they felt helped them to be more effective parents, such as learning to avoid blaming themselves or their child for the self-harm and developing new ways to communicate with their child. Parents were generally eager to pass their knowledge on to other people in the same situation. Conclusions Parents reported changes in their parenting behaviours after the discovery of a child's self-harm. Professionals involved in the care of young people who self-harm might use this information in supporting and advising parents.